Volume 1: Fuels and Combustion, Material Handling, Emissions; Steam Generators; Heat Exchangers and Cooling Systems; Turbines, 2014
DOI: 10.1115/power2014-32165
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of Waste Heat Recovery Unit Using Carbon Dioxide as Cooling Fluid

Abstract: This paper describes design and optimization of a Waste Heat Recovery Unit (WHRU) for a power cycle which uses CO2 as a working fluid. This system is designed for offshore installation to increase gas turbine efficiency by recovering waste heat from the exhaust for production of additional power. Due to severe constraints on weight and space in an offshore setting, it is essential to reduce size and weight of the equipment to a minimum. Process simulations are performed to optimize the geometry of the WHRU usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Other authors evaluate optimal designs based on techno-economic optimization (Pierobon et al, 2013;Nguyen et al, 2014a;Nguyen et al, 2014b;Pierobon et al, 2014a;Pierobon et al, 2014b;Zhang et al, 2018), albeit cost is highly uncertain in off-shore oil and gas applications. Skaugen et al (2014) developed a methodology for optimizing total minimum weight of an off-shore waste heat recovery unit by including both the finned tube bundle and the casing and structures. The result showed a close to quadratic exhaust gas flow area to keep the total weight low.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors evaluate optimal designs based on techno-economic optimization (Pierobon et al, 2013;Nguyen et al, 2014a;Nguyen et al, 2014b;Pierobon et al, 2014a;Pierobon et al, 2014b;Zhang et al, 2018), albeit cost is highly uncertain in off-shore oil and gas applications. Skaugen et al (2014) developed a methodology for optimizing total minimum weight of an off-shore waste heat recovery unit by including both the finned tube bundle and the casing and structures. The result showed a close to quadratic exhaust gas flow area to keep the total weight low.…”
Section: Introductionmentioning
confidence: 99%
“…Weight-and volume minimization of the heat exchanger core is vital due to the lack of space on these installations. Earlier work has indicated that overall Waste Heat Recovery Unit (WHRU) skid weight can be reduced by bringing down the tube diameter [1], which calls for an extension of the validity range of existing thermal-hydraulic design correlations. It is also highly desirable to be able to validate the performance of a thermally optimized design by detailed numerical modeling, before investing in fabrication and experimental testing.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for pressure drop measurements, where uncertainties are larger. Earlier work has shown that the WHRU skid weight can be reduced by scaling down the tube diameter to about 10 mm [4]. This requires new correlations with an extended validity range, to avoid extrapolation.…”
Section: Introductionmentioning
confidence: 99%